A NEW SPECIES OF ZEUGOPHORA KUNZ~ FROM JAVA (COLEOPTERA: CHRYSOMELIDAE: MEGALOPODINAE) - Reid, C. A. M. (Treubia, 2015)
Zeugophora javana sp, n. is described from West Java and placed in the subgenus Pedrillia. Diagnostic characters are given to separate Z. javana from other species in Australia.